2019
DOI: 10.1021/acs.jpca.9b00409
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Excited-State Dynamics of Eosin Y Photosensitizers Using Single-Molecule Spectroscopy

Abstract: The intersystem crossing and dispersive electron-transfer dynamics of eosin Y (EY) photosensitizers are probed using single-molecule microscopy. The blinking dynamics of EY on glass are quantified by constructing cumulative distribution functions of emissive (“on”) and nonemissive (“off”) events. Maximum likelihood estimation (MLE) and goodness-of-fit tests based on the Kolmogorov–Smirnov (KS) statistic are used to establish the best fit to the blinking data and differentiate among competitive photophysical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…For example, the molecule shown in Figure 2d exhibits 10 distinct intensities, including six on and six off events and an υ event of 0.070 s −1 . The corresponding t on range from 150 ms to 23.43 s and t off values span from 70 ms to 131.02 s. The observation that the blinking dynamics of EY demonstrate multiple emissive intensities is consistent with prior single-molecule studies of xanthene and anthraquinone dyes on glass 50,57 and TiO 2 , 24,25 which has been attributed to dynamic fluctuations in excitation, emission, and/or non-radiative decay. Overall, the substrate-dependent emission behavior of EY is consistent with a blinking mechanism that involves injection to TiO 2 to populate a non-emissive radical cation state of the dye.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For example, the molecule shown in Figure 2d exhibits 10 distinct intensities, including six on and six off events and an υ event of 0.070 s −1 . The corresponding t on range from 150 ms to 23.43 s and t off values span from 70 ms to 131.02 s. The observation that the blinking dynamics of EY demonstrate multiple emissive intensities is consistent with prior single-molecule studies of xanthene and anthraquinone dyes on glass 50,57 and TiO 2 , 24,25 which has been attributed to dynamic fluctuations in excitation, emission, and/or non-radiative decay. Overall, the substrate-dependent emission behavior of EY is consistent with a blinking mechanism that involves injection to TiO 2 to populate a non-emissive radical cation state of the dye.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…These t off are much longer than the reported T 1 lifetime of EY (i.e., 55 μs in water, 54 3.6 ms in polymethyl methacrylate, 55 and 1 ms on alumina 56 ), suggesting that another dark state is operative. The blinking dynamics of EY on glass, which has been attributed to electron transfer to trap states, 57 is quite differentwith molecules exhibiting longer t on and smaller υ event on glass as compared to TiO 2 . For example, the molecule shown in Figure 2d exhibits 10 distinct intensities, including six on and six off events and an υ event of 0.070 s −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…R6G and QD are commonly employed in single-molecule experiments and are known to exhibit, on average , qualitative differences in blinking. However, several studies have shown the blinking behavior of R6G and QD on glass to be quite dispersed (i.e., with single-emitter events ranging from milliseconds to >100 s in duration and blinking statistics that are lognormally and power-law distributed). This photophysical heterogeneity, which originates from dispersive charge-transfer processes arising from both static and dynamic variations in structure and energetics of the emitter and its local environment, is sufficiently broad to be representative of a complex “real world” sample for this initial investigation. To evaluate the BBM concept, we quantify the blinking statistics of hundreds of R6G and QD emitters to develop a classification metric.…”
mentioning
confidence: 99%
“…[1][2][3] In typical dye-sensitized HER, a dye photosensitizer and an electrocatalyst are employed together with a sacrificial electron donor. [4], [5] One of the most commonly used photosensitizer dyes for HER is Eosin Y (EY, 2',4',5',7'-tetrabromofluorescein), which undergoes photoexcitation on a comparatively fast timescale of ps-ns. [5] Next, (in case of reductive quenching of the excited state) the photosensitizer/dye accepts electrons from the sacrificial donor.…”
Section: Introductionmentioning
confidence: 99%
“…[4], [5] One of the most commonly used photosensitizer dyes for HER is Eosin Y (EY, 2',4',5',7'-tetrabromofluorescein), which undergoes photoexcitation on a comparatively fast timescale of ps-ns. [5] Next, (in case of reductive quenching of the excited state) the photosensitizer/dye accepts electrons from the sacrificial donor. [6][7][8][9] In the following step, a designated HER catalyst then transfers the photogenerated electron from the photosensitizer to the surface-adsorbed protons/hydrogen to generate H2 gas at longer timescales (~ms-s) [5,[10][11][12] and consecutively the photosensitizer/dye reverts back to the ground state.…”
Section: Introductionmentioning
confidence: 99%